Les Wallons et les Flamands devant les problèmes culturels - Allard, Jean; Bayens, Herman; Becquet, Charles-François; Craeybeckx, Lode; Van Haegendoren, Maurits; Lamberty, Max; Van Elslande, Renaat; Merecy, Renaat; Harmel, Pierre (Bruxelles : Fondation Charles Plisnier, 1958)
Bibliotheek Camille Huysmans
Frans
Monografie
Keywords: federalisme; gemeenschapsonderwijs; cultuur